Lecturers’ Perception on The Use of Blended Learning Strategy in University of Ilorin, Nigeria - Charles Olabode Olumorin; Habibat Abubakar yusuf; Mariam Abdulwasiu; Margaret Funke Farem; Adegoke Adedeji Aderogba (MO.RI Publishing, 2023)
Blended learning strategy is an education strategy that involves multiple teaching methods to help students learn more effectively, it combines a mix of face-to-face classroom instruction and online instructional approaches. Despite the importance of blended learning strategy, it has not been fully adopted by university lecturers. Hence, this study investigated Lectures’ Perception on the use of Blended Learning Strategy in University of Ilorin Nigeria. This study adopted a descriptive research design of the survey type, and employed four sectioned researcher-designed questionnaires to elicit information from the respondents.150 lecturers across seven faculties in University of Ilorin were randomly sampled for the study. Both descriptive and inferential statistics were employed to answer and test the formulated hypothesis at 0.05 level of significance. The findings of this study were: (i) The lecturers’ perception on the usefulness of blended learning strategy for instruction in University of Ilorin is positive (3.49>2.44); (ii) The lecturers’ perception on the ease of use of blended learning strategy for instruction in University of Ilorin is positive (3.35>2.44); (iii) The lecturers are facing challenges in using blended learning strategy for instruction (3.20>2.44); (iv) There was no significance difference on lecturers’ perceived usefulness of blending learning strategy based on the area of specialization (p=.060>0.05); (v) There was significance difference on lecturers’ perceived ease of use of blending learning strategy based on the area of specialization (p=.049<0.05) and (vi) There was no significant difference on lecturers’ perceived ease of use of blended learning strategy based on gender (p=.851> 0.05). Based on the findings of the study, it was revealed that blended learning is an effective strategy for quality teaching and learning. Though there are challenges affecting the proper implementation of this strategy. The study therefore recommended that seminar and workshop should be organized for lecturers to further their knowledge on the uses of blended learning strategy for instruction.